Strategi Penurunan Non Revenue Water (NRW) melalui Analisis Neraca Air dan Indikator Kinerja NRW pada Jaringan Distribusi SPAM Cabang Karawang - Zafira, Athaya Dhiya; Nurhayati, Ervin; Novianus R.P, Gabriel (Universitas Tanjungpura, 2023)
Perumdam Tirta Tarum as a BUMD with healthy performance and has FCR (Full Cost Recovery), but the NRW (Non Revenue Water) score is still quite high at 32.16%. The Karawang branch is the largest contributor to the volume of water loss, around 33% of the total water loss in 19 Branches/IKK units in other service areas. This study uses water balance analysis methods and NRW performance indicators to formulate recommendations for NRW reduction programs. Annual water loss during the period April 2022 to March 2023 was 23.96% with a loss volume of 2,343,756m3/12 months. The percentage of physical water loss is 18.49% and non-physical water loss is 5.47%. When converted to cost values, the annual loss of non-physical water is Rp.2,610,791,315.- and the annual loss of physical water is Rp.8,640,197,936.-. Physical loss is classified as category C performance (severe leakage) and the overall ATR performance indicator is classified as category C (poor ATR condition). Recommendations or strategies for handling NRW efficiently at study locations can be formulated after understanding the causes of NRW and the most influencing component factors.